PO 18219 - Treatment of malleolar ankle fractures: mapping systematic reviews - Fernandes Araujo, Caio Augustus; Kenzo Arie, Eduardo; Mizusaki, Danilo; Stella Peccin, Maria; de Almeida Estevam, Jhony; Souza de Barros, Brenison (Scientific Journal of the Foot & Ankle, 2019)
Objective: Given the epidemiological importance of malleolar fractures and differences in treatment choices, this study provides an update on the multiprofessional treatment of these fractures by mapping systematic reviews available in the scientific literature. Methods: The search was performed in the electronic databases Cochrane Database of Systematic Reviews (CDSR), Medline and Lilacs and in the PROSPERO international prospective register of systematic reviews, with no language or publication date restriction. The most recent search was performed on June 1, 2018. The term “ankle fracture” was used in those databases. Pubmed was also searched, using the [Mesh] term. The inclusion criteria were systematic reviews on the treatment of malleolar ankle fractures in adults. Results: Twenty-two systematic reviews were identified in the searched databases. Systematic reviews on the multiprofessional treatment of patients with malleolar fractures addressed the selection of metallic syndesmotic screw rather than absorbable screw without indicating its removal in the absence of symptoms. Furthermore, the Adelaide Fracture in the Diabetic Ankle (AFDA) algorithm was established for the diagnosis and treatment of diabetic patients. There is still no evidence that arthroscopically assisted open reduction and internal fixation (ORIF) is the best therapeutic method, nor is there biomechanical evidence that the locking plate is better than the conventional plate for treating lateral malleolar fracture in elderly people. There is strong evidence that mobility and early weight-bearing directly affect the functional prognosis of patients. Conclusion: This study was extremely important for identifying and selecting the most recent systematic reviews on the topic, thereby guiding practices regarding the best therapeutic regimen for patients with malleolar fractures.